Analysis of COVID-19 as a predisposing factor for acute pancreatitis: an integrative literature review (Research, Society and Development, 2023)
Objectives: The main objective of this study is to analyze the pathophysiological mechanisms present in patients with COVID-19 who developed acute pancreatitis. Secondarily, we seek to assess its clinical status and understand the current epidemiology of this pathology in a post-COVID-19 scenario. Methods: This study is an integrative literature review, in which the keywords “pancreatite aguda” and “COVID-19”, their variants and combinations in English in the PubMed and SciELO databases were used. As inclusion criteria, randomized clinical trial, case-control, cohort and cross-sectional studies were selected. Researches with patients of all ages, with publication period from 2020 and in Portuguese, English and Spanish were selected. Results: Nine articles were selected for this integrative review, 44% of which were cross-sectional (n = 4) and 66% were cohort (n = 5). Discussion: It is believed that pancreatic damage parallels disease severity in patients with COVID-19. This may be due to mechanisms of the virus itself, the host response or drugs used to treat COVID-19. Still, most patients present with a severe clinical picture and altered laboratory tests. Conclusion: The patients in the analyzed articles presented laboratory findings compatible with the picture of acute pancreatitis, in addition to the characteristic clinical picture and variable evolution. More primary studies are needed with larger and more homogeneous populations to understand how the relationship between the two diseases actually occurs.